EDUCATIONAL SOCIAL WORK IN THE FIELD OF SENIORS STUDENTS LEISURE - Т. Ковальчук; Д. Короткова (Київський національний університет імені Тараса Шевченка, 2017)
Abstract. Actuality of the theme is evergrowing due to rising social tension in society, spread of alcoholism, drug addiction, ludomania, smoking, prostitution, crime and suicide, aggravation of the crisis in the spiritual life of the family, increasing numbers of orphans and children with disabilities in physical and mental development and behavior and those who have experienced violence, street children, AIDS patients and those with poor health. The severity of these problems increases relevance of finding ways to address them, including professional tools in the field of social and educational work conserning seniors leisure. The goal of this article is to teoretically justify and experimentally test the effectiveness of organizing social and educational work in the field of seniors leisure. The research objectives were: analysis of psychological and educational literature in the field of leisure; consideration of social and educational essense and structure of recreation for children of high school age; determining the forms, methods and technologies of socio-pedagogical work, concerning leisure in high school ; development of guidance on social and educational work in the field of seniors leisure. The object is a social and educational work in the field of seniors leisure, the subject of the study – the content, forms and methods of work. This paper highlights heoretical aspects of social and educational work in the field of seniors leisure. It analyzes psychological and pedagogical literature on the study. Assesses a problem of attracting high school students to meaningful leisure and cognitive factors that affect organization of mass leisure activities at school. Develops methodical recommendations for social pedagogs on organization of seniors leisure. Evaluates the results of experiment on free time spending by seniors of Kiev secondary schools.Further theoretical study is required on topics of semantic principles of training specialists of social and educational work in the field of seniors leisure (ethnology, patriotic, spiritual, moral, ethical, artistic and aesthetic, environmental components etc).

Висвітлено теоретичні аспекти організації соціально-педагогічної роботи у сфері дозвілля старшокласників. Досліджено проблему залучення старшокласників до змістовного пізнавального дозвілля та чинники, що впливають на проведення дозвілля у школі. Розроблено методичні рекомендації для соціального педагога з організації змістовного дозвілля старшокласників. Отримано результати дослідно-експериментальної роботи проведення вільного часу дітей старшого шкільного віку київських загальноосвітніх навчальних закладів. Визначено чинники, що впливають на масовість і змістовність проведення дозвілля у школі.
СОЦІАЛЬНО-ПЕДАГОГІЧНА РОБОТА У СФЕРІ ДОЗВІЛЛЯ СТАРШОКЛАСНИКІВ
Keywords: дозвілля; дозвіллєва діяльність; сфера дозвілля; соціально-педагогічна робота; старшокласники; загальноосвітній навчальний заклад; leisure; recreational activities; field of leisure; socio-pedagogical work; high school students; secondary school